The effect of labour tightness on wages at the regional level in Central Europe - Lajos Tamás Szabó (Journal for Labour Market Research, 2024)
I estimate the effect of tightness on wages in Hungary and Slovakia. The Mortensen Pissarides model predicts a positive relationship but the empirical evidence is scarce. I instrument tightness by the distance of a district from the Austrian border, interacted with a dummy that marks the opening of the Austrian labour market to these countries in 2011. I find a positive effect of tightness on wages, which is in line with the conclusion of the models. If tightness increase by 1 per cent than ceteris paribus wages increase by roughly 0.2 per cent both in Hungary and Slovakia as well.
Keywords: J31; J61; J63; J64; 330; Labour market tightness; Local labour markets; Wage equation